Functional Identification of Complement Factor D and Analysis of Its Expression during GCRV Infection in Grass Carp (Ctenopharyngodon idella) - Chunhua Ding (MDPI AG, 2021)
Complement factor D (Df) is a serine protease well known for activating the alternative pathway (AP) in mammals by promoting the cleavage of complement component 3 (C3), thus becoming involved in innate defense. In teleost fish, however, the functional mechanisms of Df in the AP and against pathogen infection are far from clear. In the present study, we cloned and characterized the Df gene, CiDf, from grass carp (Ctenopharyngodon idella) and analyzed its function in promoting C3 cleavage and expression changes after grass carp reovirus (GCRV) infection. The open reading frame of CiDf was found to be 753 bp, encoding 250 amino acids with a molecular mass of 27.06 kDa. CiDf harbors a conserved Tryp_SPc domain, with three conserved residues representing the catalytic triad and three conserved binding sites in the substrate specificity pocket. Pairwise alignment showed that CiDf shares the highest identity (96%) and similarity (98%) with Df from Anabarilius grahami. Phylogenetic analysis indicated that CiDf and other fish Dfs formed a distinct evolutionary branch. Similar to most Dfs from other vertebrates, the CiDf gene structure is characterized by four introns and five exons. The incubation of recombinant CiDf protein with grass carp serum significantly increased the C3b content, demonstrating the conserved function of CiDf in the AP in promoting C3 cleavage, similar to Dfs in mammals. CiDf mRNA expression was widely detected in various tissues and levels were relatively higher in the liver, spleen, and intestine of grass carp. During GCRV infection over a 168-hour period, a high level of CiDf mRNA expression in the liver, spleen, and intestine was maintained at 144 and 168 h, suggesting AP activity at the late stage of GCRV infection. Collectively, the above results reveal the conserved structure and function of CiDf and its distinct expression patterns after GCRV infection, which provide a key basis for studying the roles of Df and AP during GCRV infection in the grass carp C. idella.